Odpowiedź :
a) ( x+4)+(2x-6) = x+4+2x-6=3x-2
b) -(2y+3y)+(-4y +3x +1) =-2y-3y-4y+3x+1=3x-9y+1
c) - (x-2xy)-(4x+xy)+(xy-x)=-x+2xy-4x-xy+xy-x=-4x+2xy
d) (x²+2x +1)-(x²-4x+3)=x²+2x+1-x²+4x-3=6x-2
b) -(2y+3y)+(-4y +3x +1) =-2y-3y-4y+3x+1=3x-9y+1
c) - (x-2xy)-(4x+xy)+(xy-x)=-x+2xy-4x-xy+xy-x=-4x+2xy
d) (x²+2x +1)-(x²-4x+3)=x²+2x+1-x²+4x-3=6x-2
a)=3x-2
-b)=-2y+3y+4y+3x+1=5y+3x+1
c)-x+2xy-4x-xy+xy-x= -6x +2xy
d)x (do 2) +2x+1-x(do 2 potegi)+4x-3 =-2 +6x
-b)=-2y+3y+4y+3x+1=5y+3x+1
c)-x+2xy-4x-xy+xy-x= -6x +2xy
d)x (do 2) +2x+1-x(do 2 potegi)+4x-3 =-2 +6x
a)
( x+4)+(2x-6) = 3x-2
b)
-(2y+3y)+(-4y +3x +1) = -9y+3x+1
c)
-(x-2xy)-(4x+xy)+(xy-x)=-xy-(5x+y)+y
d)
(x²+2x +1)-(x²-4x+3)=-2x+4
Wg. mnie najłatwiejsza postać.
( x+4)+(2x-6) = 3x-2
b)
-(2y+3y)+(-4y +3x +1) = -9y+3x+1
c)
-(x-2xy)-(4x+xy)+(xy-x)=-xy-(5x+y)+y
d)
(x²+2x +1)-(x²-4x+3)=-2x+4
Wg. mnie najłatwiejsza postać.